Mathematical biology Spatial Models and Biomedical Applications - Murray, J D (Springer, 2003)
Since the first edition of this book, the field of mathematical biology has established itself as a distinct discipline. Mathematical modelling is now being applied in every major discipline in the biomedical sciences. Therefore for this new edition Murray is covering certain items in depth, giving new applications such as modelling marital interaction, growth of cancer tumours, temperature sex determination, wolf territoriality and wolf-deer survival etc. In other areas he discusses basic modelling concepts and provides further references as needed. He also provides even closer links between models and experimental data throughout the text. The book presents a broad view of the field of theoretical and mathematical biology and gives an excellent background from which to begin genuine interdisciplinary research in the biomedical sciences.